Koncepcja wcielonego zła w powieściach „Mistrz i Małgorzata” M. Bułhakowa i „Portret Doriana Graya” O. Wilde’a (próba analizy porównawczej) - Chudzińska-Parkosadze, Anna (Slavia Occidentalis, 2014)
The article deals with the problem of the embodiment of evil in the novels The Master and Margarita by Mikhail Bulgakov and The Picture of Dorian Gray by Oscar Wilde. The concept is represented by the image of Lord Henry Wotton in Wilde’s novel and of Woland in Bulgakov’s novel. Both of the heroes reveal the characteristic features of the devil. However, as proves the research, the role of the devil plays Lord Henry, deluding his younger and naive friend Dorian by the luring paradoxes, and driving him to commit the murder. On the other hand, Woland turns out to be a real savior to Master, as he manages to rescue him and his beloved Margarita from the Moscow realm of hell. Moreover, Woland is a symbolic figure that stands for Lucifer, the patron of alchemic initiation.